In Vivo Dosimetry pada Radioterapi Menggunakan Teknik Modulated Arc Therapy (VMAT) dan Intensity Modulated Radiation Therapy (IMRT) - Ningrum, Rilla Ilma; Muliyana, Muliyana; Putri, Erlinda Ratnasari (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2025)
Radiation therapy is an effective method for treating cancer by using ionizing radiation to kill cancer cells or treat tumors. In radiation therapy planning, effective techniques are essential to ensure maximum dose to the tumor while protecting surrounding healthy tissue. In vivo dosimetry (IVD) measures the radiation dose received by cancer patients during therapy to ensure accurate delivery. This study reviews prior research comparing various dosimeters used in Volumetric Modulated Arc Therapy (VMAT) and Intensity Modulated Radiation Therapy (IMRT). The methodology involved a literature review of articles published between 2013 and 2023, focusing on in vivo dosimetry in VMAT and IMRT. The articles were sourced from databases like Google Scholar, ResearchGate, ScienceDirect, Elsevier, and PubMed. The findings suggest that dosimeter EPID shows significant effectiveness in detecting and verifying radiation doses in both VMAT and IMRT. Overall, VMAT demonstrates superior accuracy, consistent dose distribution, and better dose limitation to at-risk organs compared to IMRT. This study supports the use of VMAT for enhancing safety and accuracy in radiation therapy, providing a framework for policy improvements in radiotherapy services.